Kompres Hangat Dan Kompres Jahe Terhadap Penurunan Skala Nyeri Pada Pasien Rematik - Ratnawati Ratnawati; Fadli Husain; Farman Biki (Poltekkes Kemenkes Gorontalo, 2020)
Background: Rheumatic disease is a chronic systemic inflammatory disease in the joints of the body, which has clinical symptoms in the form of joint pain disorders accompanied by stiffness, redness, and swelling and is chronic. One of the treatments to deal with pain is by stimulating heat on the part of the body that is experiencing pain, including by giving warm compresses and ginger compresses which can have a warm effect on the body. Objective: This study aims to identify differences in the effectiveness of warm compresses and ginger compresses on reducing pain scale in rheumatic patients.Methods: This study uses a quasi-experimental design method with a non-equivalent control group design. The sampling technique used is quota sampling. The number of samples studied were 40 respondents, who were divided into two treatment groups. The first group was given a warm compress treatment and the second group was given a ginger compress treatment.Results: The results of the study and analysis using the Independent T-Test statistical test with a significance degree of : 0.05. The results showed that the p-value was 0.024, so H0 was rejected.Conclusion: Based on the results of the study, it can be concluded that there are differences in the effectiveness of warm compresses and ginger compresses on reducing pain scale in rheumatic patients where ginger compresses are more effective than warm compresses with an average difference of 1.25 pain scale.